1999
DOI: 10.1180/000985599546460
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and chemical characteristics of five nontronites and Fe-rich smectites

Abstract: Five Fe–bearing dioctahedral smectites (three nontronites and two Fe-rich smectites) were purified using a variety of physical and chemical procedures. The structural formulae indicate one nontronite and one Fe-rich smectite to be montmorillonitic, whereas the other three smectites are beidellitic. Mössbauer spectra showed Fe to be exclusively trivalent and were fitted with three doublets, two of which had quadrupole splittings characteristic of Fe3+ in octahedral coordination, whereas the third had a distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 59 publications
6
43
1
1
Order By: Relevance
“…These features are characteristic of Fe-rich montmorillonites with Mg (and/or probably Ni) in the octahedral sites and indicate that Fe, Mg (and/or probably Ni) may occur in adjacent octahedral sites responsible for the heterogeneity of the samples. The IR spectra of Niquelândia dioctahedral smectite (ASL-I5, CSL-G8, AS-BNi2 À Figure 5) are very similar to the Femontmorillonite characterized in weathered ultrabasic nodules in Ö lberg, Germany (Kö ster et al, 1999;Petit et al, 2002) or in pyrite-bearing calcareous sediments in the Costa Rica margin (Gaudin et al, 2005).…”
Section: Infrared Resultsmentioning
confidence: 72%
“…These features are characteristic of Fe-rich montmorillonites with Mg (and/or probably Ni) in the octahedral sites and indicate that Fe, Mg (and/or probably Ni) may occur in adjacent octahedral sites responsible for the heterogeneity of the samples. The IR spectra of Niquelândia dioctahedral smectite (ASL-I5, CSL-G8, AS-BNi2 À Figure 5) are very similar to the Femontmorillonite characterized in weathered ultrabasic nodules in Ö lberg, Germany (Kö ster et al, 1999;Petit et al, 2002) or in pyrite-bearing calcareous sediments in the Costa Rica margin (Gaudin et al, 2005).…”
Section: Infrared Resultsmentioning
confidence: 72%
“…Th e cumulative loading weights of a PLSR prediction model display the spectral features used within the statistical prediction model (Haaland and Th omas, 1988). For the prediction of the Fe oxides signifi cant areas within the cumulative loading weights could be attributed to OH stretches of FeOOH (~3660 cm -1 , 1130 cm -1 , 890 cm -1 , 810 cm -1 ; Cornell and Schwertmann, 1996), Fe-O bending vibrations (~660-690 cm -1 , 910 cm -1 ; Cornell and Schwertmann, 1996;Koster et al, 1999), Al/Fe-OH vibrations (940 cm -1 , Madejova et al, 2002), and also to Al-OH bending vibrations at ~2300 cm -1 (Clark et al, 1990).…”
Section: Pedogenic Iron Oxidesmentioning
confidence: 99%
“…Pure tv smectites should have at least 1.0 Fe mol/f.u. Iron ions reduce the thermal stability of 2:1 clay minerals due to the reduced bond energy MgÀOH > AlÀOH > FeÀOH (Kö ster and Schwertmann, 1993). Five samples can be classified as tv but none is a pure tv montmorillonite.…”
Section: Structure Of the Octahedral Sheetmentioning
confidence: 99%
“…According to Gü ven (1988), a miscibility gap exists between montmorillonite and nontronite, the existence of which has promoted some controversy in the literature: Meunier (2005) pointed out that the b-cell dimensions of beidellite and nontronite are too different to allow a continuous series. According to Köster et al (1999), no complete solid-solution is indicated between montmorillonite and beidellite. Recent studies, however, do favor a continuous series.…”
Section: Relationships Between Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation